Self-Presenting Pada Instagram Dalam Perspektif Dramaturgi di Kalangan Mahasiswa Universitas Lambung Mangkurat - Azhari, Muhammad; Khairussalam (Huma: Jurnal Sosiologi, 2024)
Students use Instagram as the main stage to represent themselves, build identity, and interact with followers through visual features. This study aims to explore how students present themselves on Instagram social media. The approach used is descriptive qualitative, adopting Erving Goffman's dramaturgy theory. Data were obtained through observation, interviews, and documentation. The data analysis technique follows the steps of Miles and Huberman, with the stages of data reduction, data presentation, and conclusion drawing. The results revealed that students build their image as motivators on Instagram through two approaches, namely verbal and non-verbal. Verbal motivators include the use of words, such as quotes from scripture, figures, or personal expressions. Meanwhile, non-verbal motivators are related to expressions and body language that express motivation without using words. Dramaturgical analysis identifies that the front stage is where students play a social role in front of the public, trying to maintain a positive image. While the back stage is used to hide information that may be undesirable. Students use impression management techniques in their content to shape the desired image to be accepted by others. This research provides an in-depth insight into the strategies and techniques used by university students in building an image as a motivator in cyberspace, focusing on verbal and non-verbal communication through the Instagram platform. The findings stimulate further understanding of how individuals use social media to represent themselves and build identity in the context of Goffman's dramaturgy.